Political Science Thought in Aggaññasutta and Cakkavattisutta - Thangthongmadan, Sathien (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The scopes of this article is to study 1) the contents of Aggaññasutta and Cakkavattisutta, 2) to study Political Science Thought in Aggaññasutta and Cakkavattisutta. The result from to study, it is found that Aggaññasutta and Cakkavattisutta consists of content that reflects important political science concepts, namely: 1) the emergence of the state is the birth of human society. It is start from birth of family pattern, social pattern and economic model, 2) political and administrative form reflecting on the selection of state governors, style of parents selection, position of guardian Parents' roles and responsibilities. 3) The concept of the Emperor, the Emperor God is a ruler who plays an important role in healing the suffering. Nourishing the people used the principles as the main core for governing with regard to the principles of correctness as the essentials principles.